2016
DOI: 10.1021/acs.energyfuels.6b00433
|View full text |Cite
|
Sign up to set email alerts
|

Combustion and Sooting Behavior of Spark-Ignited Ethanol–Isooctane Sprays under Stratified Charge Conditions

Abstract: A spray combustion investigation within an optically accessible high-temperature/high-pressure chamber with ignition was conducted to study soot formation of ethanol blended fuels at cold start conditions. The fuels ethanol, isooctane, and its blends E85 (85 vol% of ethanol in isooctane) and E20 were studied at different temperatures under direct injection spark ignition engine stratified charge conditions. A high-speed camera in combination with an image stereoscope was used in order to visualize the combusti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…where d is the nozzle diameter, u is the jet velocity, L is the liquid kinematic viscosity, L is the liquid fuel density, and L is the surface tension of the liquid fuel. With a nozzle diameter of 168 mm and an estimated jet velocity of u ¼ 120 m/s (determined in Storch et al 2 at similar conditions), the We and corresponding Re can be deduced (see Table 2). An increase of the temperature leads to an increase in We of about 11-16%.…”
Section: Description Of the Experimentsmentioning
confidence: 99%
“…where d is the nozzle diameter, u is the jet velocity, L is the liquid kinematic viscosity, L is the liquid fuel density, and L is the surface tension of the liquid fuel. With a nozzle diameter of 168 mm and an estimated jet velocity of u ¼ 120 m/s (determined in Storch et al 2 at similar conditions), the We and corresponding Re can be deduced (see Table 2). An increase of the temperature leads to an increase in We of about 11-16%.…”
Section: Description Of the Experimentsmentioning
confidence: 99%
“…This article reports on fluorescence and absorption measurements of the dye nile red in a gasoline surrogate and in aviation fuels blended with bio-components, which was conducted to evaluate its applicability for LIF/Mie droplet sizing. For the investigations, the gasoline surrogate fuel “Toliso”, consisting of isooctane and toluene (65 vol%/35 vol%; see also Section 3 for further explanation) [1,39,40,41] mixed with ethanol (20 vol% in E20 and 40 vol% in E40), as well as four aviation fuel mixtures were analyzed. The aviation fuels studied are the base fuel Jet A-1 and blends with HEFA (30 vol% and 50 vol%) and with farnesane (10 vol%), which are approved by the ASTM for aviation applications.…”
Section: Introductionmentioning
confidence: 99%
“…This effect is also known for some iso-octane/ethanol-mixtures [ 35 ]. For example, for E20, it is found that ethanol evaporates faster than iso-octane at certain conditions, while for E85, the sequence can be in inverse [ 35 , 36 , 37 ]. Similar behavior is expected for butanol admixture.…”
Section: Resultsmentioning
confidence: 99%